Struktur Sosial pada Rumah Pejabat Tinggi Perkebunan Zaman Hindia Belanda di Jawa Bagian Barat - Lia Nuralia (Kapata Arkeologi, 2017)
This paper aims to reveal the social structure on the high officials of plantation residence in west part of Java. This paper is based on research reports using archaeological research methods, explaining about the architecture, layout, materials, and technology used to determine the symbolic meaning behind the physical form of the building. Structure concept and non-verbal communication concept can explain that the high officials of plantation residence is a central building in the plantation emplacement. The residence as a symbol of great power, especially in the plantation environment that still exist until now.Tulisan ini bertujuan mengungkap struktur sosial pada rumah pejabat tinggi perkebunan peninggalan zaman Hindia Belanda di Jawa bagian barat. Tulisan ini berdasarkan laporan hasil penelitian yang menggunakan metode penelitian arkeologi, menjelaskan tentang arsitektur, tata letak, bahan, dan teknologi yang digunakan untuk mengetahui makna simbolik dibalik wujud fisik bangunan. Structure concept dan non-verbal communication concept dapat menjelaskan bahwa rumah pejabat tinggi perkebunan merupakan bangunan sentral dalam emplasemen perkebunan. Rumah tersebut sebagai simbol kuasa besar, terutama di lingkungan perkebunan yang masih eksis sampai sekarang.